Advances in Optical and Mechanical Technologies for Telescopes and Instrumentation 2014
DOI: 10.1117/12.2055014
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized Shack-Hartmann wavefront sensors for starbugs

Abstract: The ability to position multiple miniaturized wavefront sensors precisely over large focal surfaces are advantageous to multi-object adaptive optics. The Australian Astronomical Observatory (AAO) has prototyped a compact and lightweight Shack-Hartmann wavefront-sensor that fits into a standard Starbug parallel fibre positioning robot. Each device makes use of a polymer coherent fibre imaging bundle to relay an image produced by a microlens array placed at the telescope focal plane to a re-imaging camera mounte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The use of polymer imaging bundles becomes an attractive solution to distributed wavefront sensors, where each bundle has miniature Shack-Hartmann fore-optics, relaying the wavefront information to a high frame rate camera situated off the focal plane. These miniature Shack-Hartmann wavefront sensors (mini-SHWFS; Goodwin et al 2014) were demonstrated on the 3.9 m AAT in December 2015 (see Figure 8; a full description of these devices is provided by Goodwin et al in preparation).…”
Section: Multi-object Wavefront Sensingmentioning
confidence: 99%
“…The use of polymer imaging bundles becomes an attractive solution to distributed wavefront sensors, where each bundle has miniature Shack-Hartmann fore-optics, relaying the wavefront information to a high frame rate camera situated off the focal plane. These miniature Shack-Hartmann wavefront sensors (mini-SHWFS; Goodwin et al 2014) were demonstrated on the 3.9 m AAT in December 2015 (see Figure 8; a full description of these devices is provided by Goodwin et al in preparation).…”
Section: Multi-object Wavefront Sensingmentioning
confidence: 99%
“…The ability to position multiple miniaturised wavefront sensors precisely over a large focal surface is advantageous to understand the localized wavefront distortions through the atmosphere and telescope. The AAO has prototyped a compact and lightweight Shack-Hartmann wavefront-sensor that fits into a standard Starbug robot [11]. Each sensor makes use of a polymer fibre bundle to relay an image produced by a microlens array placed at the telescope focal plane in the Starbug to a re-imaging camera mounted elsewhere.…”
Section: Wavefront Sensing Starbugsmentioning
confidence: 99%
“…MANIFEST is a robotic fibre positioning system designed for the Giant Magellan Telescope. The MANIFEST instrument concept [1][2][3] consists of hundreds of individual robots, called Starbugs [4][5][6][7][8][9][10][11], which are moved in parallel across the full GMT 20 arcmin field-of-view to very high precision using a closed-loop metrology system. The Starbugs are adhered via vacuum force to a glass field plate located at the GMT focal plane.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to solve these challenges of focal plane positioning of multiple wavefront correction devices for ELTs for MOAO, the Australian Astronomical Observatory (AAO) has been developing the new concept of Hoverboards. The AAO has already reported on the concept of miniature wavefront sensors (WFS) for ELTs or Starbug WFS [3,10], see Figure 2. Hoverboards are the next generation robotic positioners that can move much heavier payloads than Starbugs [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hoverboard applications for the GMT include MOAO, e.g. a possible upgrade option for MANIFEST[3,7,8].…”
mentioning
confidence: 99%